Aberrantly Decreased Levels of NKG2D Expression in Children with Kawasaki Disease. (23rd April 2013) - Ge, X.; Li, C.‐R.; Yang, J.; Wang, G.‐B.
Abstract This study is designed to investigate the changes of NKG2D expression on CD8+T cells and CD3−CD56+NK cells in Kawasaki disease (KD). NKG2D/NKG2A expression on CD3−CD56+NK cells and CD8+T lymphocytes, and NKG2D ligands such as major histocompatibility complex I chain‐related molecules A(MICA) and UL‐16‐binding proteins (ULBP‐1) expression on CD14+ mononuclear cells (MC) were analysed by flow cytometry in patients with KD. Real‐time polymerase chain reaction (PCR) was used to evaluate the mRNA levels of interleukin (IL)‐1β, IL‐6 and tumour necrosis factor (TNF)‐α in CD14+ cells. Plasma cytokine [IL‐7, IL‐12, IL‐15, interferon (IFN)‐γ and transforming growth factor (TGF)‐β] concentrations were measured by ELISA. The levels of NKG2D on NK cells and CD8+T cells expression in acute phase of KD were significantly lower than those in normal controls (P < 0.05), and the levels of NKG2D expression in the patients with coronary artery lesion (KD‐CAL+) were lower than those in patients with KD‐CAL−. There was an upregulated tendency after treatment with IVIG. We found higher expression levels of proinflammatory cytokines from MC, such as IL‐1β, IL‐6 and TNF‐α in patients with KD compared with the healthy controls (P < 0.05). The concentrations of IL‐7 and IL‐15 were significantly decreased in acute phase of KD (P < 0.05) and to some extent elevated after therapy with IVIG (P < 0.05), while antagonistic cytokines like IFN‐γ were increased in acute phase of KD (P < 0.05) and reduced after therapy with IVIG (P < 0.05). These results suggest that aberrantly decreased levels of NKG2D expression on NK cells and CD8+T cells might be one of the factors led to disturbed immunological function in patients with KD. Cytokines milieu could be important factors causing reduced expression of NKG2D.